Impact of deception detection errors on public's trust in the police - Hurst-Wagner, Melanie (Legal and criminological psychology, 2012)
Purpose. The present study explored the public's attitude towards errors in police officers’ detection of deception. Based on findings on trust in the police after responses to terrorist threats, we predicted a positive influence of a correct credibility assessment and of a risk-averse response bias of police officers on public's trust. Methods. A general population sample (N= 151) read a hypothetical scenario concerning a credibility judgment and indicated their trust in the officers making the judgment. Decision outcome was manipulated by varying the four outcomes of a signal-detection task, namely, Hit, Miss, False Alarm, and Correct Rejection. Results. In line with findings on trust in the police following responses to terrorist threats, people trusted police officers more if they judged the credibility of a suspect correctly. Moreover, officers who disbelieved the suspect's statement were trusted more than officers who believed, independently of outcome correctness. Furthermore, this effect was moderated by individual differences in error weighting. Conclusions. In sum, these findings indicate that lie-biased credibility judgments made by police officers are supported by the public and increase their trust in the police. In addition, the present findings suggest that an asymmetrical weighting of judgment errors is a relevant factor in explaining the development of and attitude towards lie bias.